Media Pembelajaran Interaktif untuk Kelas 1 Sekolah Dasar Berdasarkan Kurikulum 2013 Berbasis Android - Kessy Hofany; Justinus Andjarwirawan; Lily Puspa Dewi (Jurnal Infra, 2016)
Curriculum of 2013 is a curriculum that apllied nationwide as the development of Compentency Based Curriculum (KBK) and use the system of integrative-tematic. Of course its also brings new problems for teacher and student in adapting the change of curriculum. For the teachers, the difficulties is the lack of learningmaterials when students are out of school, so students hard to learn independently and make teachers should teach more to make students can reach the existing competencies. Especially for first grade primary school student, who initially studied the learning system of kindergartens that they are more learn while playing, must begin to adapt to primary school learning system. Therefore we need media interactive learning and engaging for students.This application will provide the means for first grade primary school students to learn the curriculum in 2013 to grade 1 primary school, but in an atmosphere of playing to keep the child interested in learning albeit with new learning system. Design and manufacture of these applications based on the 2013 curriculum for grade 1 primary school with the chosen theme is the theme Diriku and theme Kegemaranku.The test results showed that the application running on the mobile device mininum Android 4.0.3 (IceCreamSandwich). This application considered beneficial because it helps the children to learn while playing and application considered attractive for children.